If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1y = 66 Solving 7x + -1y = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 7x + -1y + y = 66 + y Combine like terms: -1y + y = 0 7x + 0 = 66 + y 7x = 66 + y Divide each side by '7'. x = 9.428571429 + 0.1428571429y Simplifying x = 9.428571429 + 0.1428571429y
| -2x+-8+-7x+2= | | -3x+2y=-33 | | (x*x)+18x+5=0 | | 225-6x=30x+17 | | h=-16t^2+80t+6 | | f(x)=-0.5x^3+2.5x^2+2x-10 | | 6.4x-3.5x=-46.4 | | -5g-7=3 | | -2n-15=61 | | f(x)=x^2+5x-2(2f(2)) | | f(x)=x^2+5x-2 | | 6+10x=42 | | [2-5(6+11)]= | | -4x+9y=-27 | | -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= |